Investigation of Partamona helleri (Apidae, Meliponini) B chromosome origin. An approach by microdissection and whole chromosome painting - Martins, Cinthia Caroline Cardoso; Diniz, Debora [UNESP]; Sobrinho-Scudeler, Patricia E. [UNESP]; Foresti, Fausto [UNESP]; Campos, Lucio Antônio Oliveira; Costa, Marco Antônio (Springer Nature, 2013)
The stingless bee Partamona helleri in southeast Brazil shows the regular chromosome number 2n = 34 and a variable number of up to four minute B1 or B2 chromosomes. Previous cytogenetic analyses have indicated morphological similarities between the B1 chromosome and chromosome segments in the regular karyotype. In this study, microdissection and chromosome painting were employed along with C banding, NOR banding, and base-specific fluorochrome staining to investigate the origin of the B1 chromosome in P. helleri. B1-generated probe hybridized exclusively to B1 chromosomes. This result suggests an independent origin from the regular karyotype or, alternatively, that the B chromosome may have suffered substantial genetic alterations along its independent evolution. The absence of higher dosages of these small B chromosomes in this population of P. helleri may be related to the existence of either a genetic or cytogenetic constraint in the establishment of such high numbered karyotypes. © 2012 INRA, DIB and Springer-Verlag, France.
Keywords: B chromosome probe; Hymenoptera; stingless bee; bee; chromosome; cytogenetics; genetic variation; hybridization; karyotype; morphology; Brazil; Apidae; Meliponinae; Partamona helleri